2019
DOI: 10.1111/1759-7714.13004
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pleural effusion as a predictor of the efficacy of anti‐PD‐1 antibody in patients with non‐small cell lung cancer

Abstract: Background The aim of this study was to evaluate the usefulness of the presence of malignant pleural effusion (MPE) as a negative predictor of anti‐PD‐1 antibody efficacy. Methods A retrospective review of patients with advanced or recurrent non‐small cell lung cancer treated with an anti‐PD‐1 antibody between December 2015 and March 2018 at the National Cancer Center Hospital, Japan, was conducted. Progression‐free survival (PFS) and overall survival (OS) were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Recently, malignant pleural effusion has been associated with shorter progression-free survival and overall survival in NSCLC patients treated with anti-PD-1 antibodies. [19][20][21] Taken together, the presence of pleural effusion before treatment may be one of the noteworthy factors when considering nivolumab as a therapeutic candidate for NSCLC. The identification of abnormal change in CRP levels as a poor prognostic factor may be related to its role as a marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, malignant pleural effusion has been associated with shorter progression-free survival and overall survival in NSCLC patients treated with anti-PD-1 antibodies. [19][20][21] Taken together, the presence of pleural effusion before treatment may be one of the noteworthy factors when considering nivolumab as a therapeutic candidate for NSCLC. The identification of abnormal change in CRP levels as a poor prognostic factor may be related to its role as a marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the response rate was markedly lower in patients with pleural or pericardial metastasis than that observed in those without pleural or pericardial metastasis [11]. Shibaki et al reported that the presence of malignant pleural effusion was an independent negative predictor affecting PFS and OS, regardless of the presence of positive PD-L1 expression [12].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, these studies showed that ICI monotherapy tended to be less effective in patients with pleural effusion. However, the mechanism responsible for the low efficacy of ICIs observed in patients with pleural effusion remains to be elucidated [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the response rate was markedly lower in patients with pleural or pericardial metastasis than that observed in those without pleural or pericardial metastasis [11]. Shibaki et al reported that the presence of malignant pleural effusion was an independent negative predictor affecting PFS and OS, regardless of the presence of positive PD-L1 expression [12]. Furthermore, these studies showed that ICI monotherapy tended to be less effective in patients with pleural effusion.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, these studies showed that ICI monotherapy tended to be less effective in patients with pleural effusion. However, the mechanism responsible for the low efficacy of ICIs observed in patients with pleural effusion remains to be elucidated [11,12]. The KEYNOTE-189 study investigated patients with previously untreated metastatic non-squamous NSCLC without epidermal growth factor receptor or anaplastic lymphoma kinase mutations.…”
Section: Discussionmentioning
confidence: 99%